A review on green synthesis of silver nanoparticles and their applications. (3rd October 2017) - Rafique, Muhammad; Sadaf, Iqra; Rafique, M. Shahid; Tahir, M. Bilal
Abstract: Development of reliable and eco-accommodating methods for the synthesis of nanoparticles is a vital step in the field of nanotechnology. Silver nanoparticles are important because of their exceptional chemical, physical, and biological properties, and hence applications. In the last decade, numerous efforts were made to develop green methods of synthesis to avoid the hazardous byproducts. This review describes the methods of green synthesis for Ag-NPs and their numerous applications. It also describes the comparison of efficient synthesis methods via green routes over physical and chemical methods, which provide strong evidence for the selection of suitable method for the synthesis of Ag-NPs.